Assessment of the moral permissibility of the racial quota system in South African spot - Nash, Grant (My University, 2018)
In many countries competitive, professional and international sport selection is based primarily on athletic merit and ability. In South Africa, this is not always the case. This paper delves into the practice of the racial quota system as used in South African sport and attempts to clear the morally muddy water and answer the question: is the use of the quota system as a means to racially transform competitive sport in South Africa morally permissible? I do this by taking a look at four widely used arguments that are in favour of the racial quota system to determine if any of these arguments defeat my initial premise which is that competitive, professional and international sport selection should be based on merit-only.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts Applied Ethics for Professionals University of the Witwatersrand, Johannesburg March 2018
Keywords: Discrimination in sports--South Africa; Sports--Sociological aspects